Autologous bone marrow clot as an alternative to autograft for bone defect healing - Lim, Z. X. H. (2019)
Objectives: Long bone defects often require surgical intervention for functional restoration. The ‘gold standard’ treatment is autologous bone graft (ABG), usually from the patient’s iliac crest. However, autograft is plagued by complications including limited supply, donor site morbidity, and the need for an additional surgery. Thus, alternative therapies are being actively investigated. Autologous bone marrow (BM) is considered as a candidate due to the presence of both endogenous reparative cells and growth factors. We aimed to compare the therapeutic potentials of autologous bone marrow aspirate (BMA) and ABG, which has not previously been done. Methods: We compared the efficacy of coagulated autologous BMA and ABG for the repair of ulnar defects in New Zealand White rabbits. Segmental defects (14 mm) were filled with autologous clotted BM or morcellized autograft, and healing was assessed four and 12 weeks postoperatively. Harvested ulnas were subjected to radiological, micro-CT, histological, and mechanical analyses. Results: Comparable results were obtained with autologous BMA clot and ABG, except for the quantification of new bone by micro-CT. Significantly more bone was found in the ABG-treated ulnar defects than in those treated with autologous BMA clot. This is possibly due to the remnants of necrotic autograft fragments that persisted within the healing defects at week 12 post-surgery. Conclusion: As similar treatment outcomes were achieved by the two strategies, the preferred treatment would be one that is associated with a lower risk of complications. Hence, these results demonstrate that coagulated BMA can be considered as an alternative autogenous therapy for long bone healing.